2012
DOI: 10.1111/j.1651-2227.2012.02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Newborn feeding behaviour depressed by intrapartum oxytocin: a pilot study

Abstract: In this pilot study, intrapartum exogenous oxytocin seems to disturb sucking and breastfeeding duration. Further studies are required to confirm these results and to ascertain whether there could be other effects of intrapartum oxytocin on newborn behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 29 publications
1
52
0
1
Order By: Relevance
“…Little is known about other possible long-term effects of oxytocin administration during labor on the physiology of the mother. A recent study (42), however, has linked intrapartum exogenous oxytocin to difficulties with sucking behavior in the newborn and a decreased duration of breastfeeding. Given the role of oxytocin in lactation, the long-term effect of exogenous oxytocin on endogenous oxytocin may be relevant to explaining this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about other possible long-term effects of oxytocin administration during labor on the physiology of the mother. A recent study (42), however, has linked intrapartum exogenous oxytocin to difficulties with sucking behavior in the newborn and a decreased duration of breastfeeding. Given the role of oxytocin in lactation, the long-term effect of exogenous oxytocin on endogenous oxytocin may be relevant to explaining this finding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher synOT dosage was associated with less successful breastfeeding, as well as with the detection of ASD at six years of age ( n = 400) [74]. Similarly, higher synOT dosage has been associated with less likelihood of exclusive breastfeeding at three months, as well as less optimal sucking behaviors ( n = 20) [75]. Prefeeding behavioral cues one hour after birth have been examined in relation to synOT exposure ( n = 47).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…There is paucity of data on the effects of SynOT in newborn offspring. Some studies have found an association between SynOT peripartum exposure and increased incidence of unwanted breastfeeding cessation as well as changes in newborn offspring feeding behaviour including lower prefeeding cues, suction and swallowing. However, results in this area of research are mixed.…”
Section: Discussionmentioning
confidence: 99%